Tracer Study of Graduates of PJKR UNNES on Teacher Competence in the Field of Physical Education - Pramono, Harry; Kusuma, Donny Wira Yudha; Hartono, Mugiyo; Annas, Mohammad; S, Adi; Wijayanti, Dwi Gansar Santi (Department of Physical Education, Sport, Health and Recreation, 2023)
Alumni is a means of promotion and curriculum development of a study program. Based on this background problem, this research focuses on finding data on graduates or alumni through tracer studies. The research design uses qualitative research. The population in this study were all graduates of the Department of Physical Education, Health and Recreation (PJKR) Semarang State University. The data collection method used by researchers is: a graduate tracer study system is carried out online through the development of an